STUDI ETNOBOTANI JENIS REMPAH YANG DIGUNAKAN DALAM BUMBU MASAKAN TRADISIONAL ADAT DI KERAJAAN ROKAN KABUPATEN ROKAN HULU, RIAU - Tribudiarti, Melly; Syamsuardi, Syamsuardi; Nurainas, Nurainas (BERITA BIOLOGI, 2018)
Rokan Kingdom was a small kingdom that is now located in Rokan Hulu regency of Riau Province. This region is bordered by North and West Sumatra Province to the north. Rokan Kingdom has a diversity of Indigenous cultures and traditional as an influence of Malay, Minangkabau, Mandailing and Java ethnics. Cultural differences effect people to use variety of herbs as spice in cooking. This study aims to determine the species of plants used as spices in the traditional cuisine within Rokan Palace, Riau and to understand the use value (UV) of each plant. A field survey and interviews were conducted to obtain plant materials and determine its utilization. The voucher specimen stored at Andalas University Herbarium (ANDA), Padang, West Sumatera. Total species obtained in this study is 29 species from 17 families. All of collected plants are used in 16 traditional cuisines. Allium cepa (shallot) has the highest UV = 0.91 as the most common species used as a traditional cooking spice in Rokan Palace.